2005
DOI: 10.1055/s-2005-836792
|View full text |Cite
|
Sign up to set email alerts
|

Stellenwert und Technik der Autologen Chondrozyten-Transplantation

Abstract: The bad risk for an early onset of osteoarthritis in the knee increases with the size of a cartilage defect. A collateral meniscus- or ligament-tear will enforce this hazard in addition. In order to avoid such a development, relevant full-thickness cartilage defects should be reconstructed biologically and attendant meniscus- or ligament-tears as well as varus- or valgus deformities should be treated. A number of studies, including some prospective-randomized trials, have shown that autologous chondrocyte tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
6

Year Published

2006
2006
2008
2008

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 14 publications
0
10
0
6
Order By: Relevance
“…Mehrere Biomaterialien natürlicher oder synthetischer Herkunft [24] befinden sich für diesen Zweck mittlerweile in der klinischen Evaluationsphase, und es wurden bereits die ersten ermutigenden Ergebnisse veröffentlicht [6,21,23,31,59,69].…”
Section: Periostlappenunclassified
“…Mehrere Biomaterialien natürlicher oder synthetischer Herkunft [24] befinden sich für diesen Zweck mittlerweile in der klinischen Evaluationsphase, und es wurden bereits die ersten ermutigenden Ergebnisse veröffentlicht [6,21,23,31,59,69].…”
Section: Periostlappenunclassified
“…Grundsätzlich sollte bei Vorliegen eines Gelenkknorpelschadens eine zeitnahe Rekonstruktion angestrebt werden, da größere Knorpeldefekte in der Regel in eine Arthrose münden [1,6].…”
Section: Operative Therapieunclassified
“…Darüber hinaus ist eine Zulassung des Biomaterials für eine trägerge-koppelte ACT durch die zuständigen Stellen notwendige Voraussetzung für dessen klinischen Einsatz [1]. Ein weiterer Vorteil der matrixgekoppelten Technik liegt darin, dass sich im Vergleich zur konventionellen ACT die Zugangswege verkleinern und Schnitt-Naht-Zeiten wesentlich reduzieren lassen, wodurch sich eine geringere Komorbidität ergibt und der stationäre Aufenthalt verkürzt wird [2,6].…”
Section: Matrixassozierte Autologe Chondrozytentransplantationunclassified
“…Cell sources may be autologous chondrocytes, periosteum or mesenchimal stem cells (Wakitani et al 2002;Fritz et al 2005). Recently Grogan et al identified specific markers of monolayerexpanded chondrocytes that allow selection of highly chondrogenic subpopulations (Grogan et al 2007).…”
Section: Introductionmentioning
confidence: 99%